Is Gonococcal Paraurethral Duct Infection a Local Complication of Urethral Gonorrhea in Men?. Issue 3 (8th May 2019) - Fan, Wenge; Zhang, Qingsong; Wang, Ling; Jiang, Tingwang
Gonococcal paraurethral duct infection in males has previously been regarded as a local complication of urethral gonorrhea. To verify this, pathogens were investigated in urethral secretions from 81 male patients with gonococcal paraurethral duct infection. In patients with gonococcal infections of both the urethra and the paraurethral duct, the times of onset of the first symptoms associated with urethral gonorrheal and gonococcal paraurethral duct infection were compared. Among 81 male patients with gonococcal paraurethral duct infection, gonococci were detected in the urethras of 76 patients and no pathogens were detected in the urethras of the remaining 5 patients. The first symptom associated with urethral gonorrhea and gonococcal paraurethral duct infection occurred simultaneously in 10 cases. In 7 cases, the first symptom of gonococcal paraurethral duct infection occurred 2–4 days (2.29 ± 0.76 days) earlier than that of urethral gonorrhea and in 59 cases, the first symptom of urethral gonorrhea occurred 1–6 days (3.07 ± 1.19 days) earlier than that of gonococcal paraurethral duct infection. This study shows that gonococcal paraurethral duct infection in males can be caused by primary infection of Neisseria gonorrhoeae.